2018
DOI: 10.1021/acs.langmuir.7b03263
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphazene-Based Hybrid Nanoporous Materials as Superior Metal-Free Adsorbents for Gas Sorption Applications

Abstract: Cyclophosphazene-based inorganic-organic hybrid nanoporous materials (CHNMs) have been synthesized by a facile solvothermal method. The condensation of pyrrole with the reaction product of phosphonitrilic chloride trimer and 4-hydroxybenzaldehyde resulted in the formation of high-surface-area CHNMs. The maximum specific surface area (SA) of 1328 m g with hierarchical pore structures having micropores centered at 1.18 nm and mesopores in the range of 2.6-3.6 nm was estimated from the N sorption analysis. Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Much attention has been directed towards the separation and capture of CO 2 from various effluent gases, especially from dilute-purity sources (< 5% CO 2 ). [1][2][3] Moreover, methane( CH 4 )i sc onsidered asar elatively clean energyc ompared with other conventional fossil fuels. Natural gas reserves generally contain different amountso fC O 2 ,w hich will lower the heating value of the energy and result in pipeline corro-sion.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been directed towards the separation and capture of CO 2 from various effluent gases, especially from dilute-purity sources (< 5% CO 2 ). [1][2][3] Moreover, methane( CH 4 )i sc onsidered asar elatively clean energyc ompared with other conventional fossil fuels. Natural gas reserves generally contain different amountso fC O 2 ,w hich will lower the heating value of the energy and result in pipeline corro-sion.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphazene cyclomatrix polymers are highly cross‐linked and can be obtained by nucleophilic substitution reaction of chlorocyclophosphazenes with phenols or amines . Practical applications of these materials as efficient adsorbents for dyes, iodine or for CO 2 storage have been reported. Nevertheless, the use of phosphazene cyclomatrix materials for adsorption of metal ions has not been adequately addressed so far.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Phosphazene cyclomatrix polymers are highlyc ross-linked and can be obtained by nucleophilic substitution reactiono fc hlorocyclophosphazenes with phenols or amines. [43] Practical applications of these materials as efficient adsorbents for dyes, [44] iodine [45] or for CO 2 storage [46][47][48][49][50] have been reported. Nevertheless,t he use of phosphazene cyclomatrixm aterials for adsorption of metal ions has not been adequately addressed so far.O zcan et al have reported the synthesis of phosphazene microspheres by reacting hexachlorocycltriphosphazene( HCCP) or octachlorocycltetraphosphazene (OCCP) with diaminodiphenylmethane [51] and demonstrated their use for removal of Pb 2 + ions from water.L iet alh ave reported the application of ap orousp hosphazene-based crosslinked polymerf or effective extraction of uraniumi ons from water.T he hybrid polymer was prepared by reacting HCCP with phenylenediamine, hydroquinone and phlorogluci-nol.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, it has been widely used in the field of battery, adsorption, mechanical functional materials and so on. Nanoporous materials based on poly ionic liquid had dual advantages of porous materials and poly ionic liquids, and had already been applied on organic catalytic reactions, batteries and functional materials . Thus, it is probably likely that porous materials have been considered as the most promising catalysts for alkylation.…”
Section: Introductionmentioning
confidence: 99%